The Raman Spectroscopy and XPS investigation of CVD diamond after fast-neutron irradiation. (March 2020) - Liu, You-hang; Zhang, Jia-liang; Wu, Fang-liang; Qi, Ming; Hei, Li-fu; Lv, Fan-xiu
Graphical abstract: Highlights: We study the surface Raman Spectra, cross-section Raman spectra and XPS results of differently treated diamond samples. The XPS spectra of fast-neutron irradiated diamonds are given for the first time to the best of our knowledge. We propose that the Raman peak at 1200 cm −1 may be ascribed to the satellite peak due to the Fano effect. We propose that there may be more oxygen-terminated groups formed on the irradiated diamond surfaces after acid cleaning. We propose that the introduced oxygen atoms in oxygen-terminated groups could provide carriers for Fano interference. Abstract: Artificial diamonds grown by the method of chemical vapor deposition (CVD) were investigated using Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) after they were irradiated with fast neutrons up to a fluence of 3.3 × 10 17 neutrons/cm 2 . Compared with the unirradiated one, the Raman spectra of irradiated diamonds showed a broadening and asymmetric Raman peak shape. In addition, there is a new peak at 1200 cm −1 in the irradiated-surface Raman spectra, which can be attributed to the satellite peak due to Fano interference. The XPS results showed that more ether bonds will be formed on the surface of irradiated diamonds after acid cleaning, and the introduced oxygen atoms also provide carriers for the Fano effect.